Study of pregnancy with disseminated intravascular coagulation - Kadikar, Satishchandra K.; Diwan, Farheenbanu J.; Topiwala, Usmaan; Agasiwala, Saliha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: At present time, obstetric bleeding remains to be the world’s main cause of maternal mortality, early identification of factors leading to haemorrhage and early management of underlying pathological process is the key stone of the treatment. The most important pregnancy related condition leading to bleeding with high maternal mortality and morbidity rate is disseminated intravascular coagulation (DIC). Methods: A prospective study of 50 cases of pregnancy with DIC was performed from May 2018 to November 2020 in our institute to detect the various aetiology and complications associated with DIC leading to maternal mortality and morbidity and study perinatal outcome in pregnant women with DIC. Results: The prevalence of DIC in our institute is 0.22%. Common causes of DIC were abruption (36%), haemorrhage (34%), preeclampsia (18%), sepsis (6%) and acute hepatic failure (6%). The composite severe maternal morbidity outcome in haemorrhage (100%), abruption (63%), preeclampsia (58%), and AVH (33%).Out of the three most common causes (abruption, haemorrhage and preeclampsia), the composite maternal morbidity outcome was significantly more in women with haemorrhage than with abruption and preeclampsia. Conclusions: DIC, as a marker of severe obstetrical complications, is associated with high levels of mortality and morbidity. Recognition of the antecedent causes and early investigation for and active management of DIC may help lower this morbidity.